Os principais fatores de risco nas diferentes fases do ciclo de vida dos projetos de capital em uma empresa de mineração nacional de grande porte - Mulisani, Roberto Vendramini (2013)
The prospects for moderate expansion in global demand for minerals and metals in the medium term lead companies in the mining sector to focus its investments on increasing their efficiency while minimizing their costs. The increasing complexity of projects given the multiplicity of influences and factors both internal and external, makes these companies seek efficiency in the performance improvement of the management of this project. Investments focused on world-class assets, able to create value over the cycle and having long life, low cost, with expansion possibilities and production of high quality allow the optimization of the management of capital. However, large uncertainties that affect these projects at all stages of its development to its implementation, have demanded a risk management important to achieve the company's strategic objectives. The identification of a maximum number of risks, prioritizing and quantifying their impact processes are central to good risk management in projects. This study presents, as a case study, the main research risks that fall in capital projects of a national mining company large. The company has applied an average of US$ 16 billion a year in new facilities and technology improvements to their operations. Interviews with project managers, survey data based on reports of workshops focusing on risk management of various capital projects, as well as search the database of the company, which allowed us to know in depth the major internal and external risks that affect different stages or phases of development of these projects. The result of this research will enable raise knowledge on the risk management of projects in companies mining segment. How important contribution, the findings of this study allow greater precision in determining the contingency fund applied in strategic and financial planning of these risks, which become known within the context presented in this research.